Knowledge and practice of Chinese physicians toward carbapenem-resistant enterobacteriaceae: a nationwide cross-sectional survey in top 100 hospitals - Shi, Qingfeng; Pan, Jue; Ma, Yuyan; Hu, Bijie; Gao, Xiaodong (Journal of Thoracic Disease; Vol 10, No 7 (July 31, 2018): Journal of Thoracic Disease, 2018)
Background: Carbapenem-resistant enterobacteriaceae (CRE) has been one of the greatest threats to population health over the past decade. Few reports have focused on the knowledge and practice of Chinese physicians toward CRE. Methods: A cross-sectional survey of CRE-related knowledge and practice was conducted in top 100 tertiary comprehensive hospitals between June and July 2017. Results: A total of 53 designed hospitals responded, including 217 intensive care unit physicians, 142 respiratory physicians, 112 hematology physicians, and 58 infectious disease physicians. The percentage of correct answers to each questions ranged from 25.7% to 89%, and the physicians’ knowledge score ranged from 1 to 9 (median =6; interquartile range, 5–7). A significant relationship was found between CRE knowledge level and demographics of city level, work department, and CRE treated in the last 6 months. In terms of practice, physicians with a high knowledge level were more likely to treat CRE infection with combined medication, considering undesirable infection control practice as the main risk factor. Conclusions: Overall, majority of physicians were concerned about CRE infections and indicated that they would take measures to prevent this gram-negative resistant bacteria. The findings will help focus and target on teaching and awareness-raising strategies.